Jus Puniend in the Administrative Disciplinary Process - Campos, Adir Claudio (2020)
The punitive power of the State, whether in the judicial sphere or in the administrative sphere, must be in accordance with the constitutional guarantees based on the binomial dignity of the human person and due process to the idea. of the rationality of human behavior to the modern state. The two principles of justification and punishment are the reasonableness and the proportion suffered progressive and unreliable when the public administration exorbitates from punishing its public servants. legal, and that crystallized in principles erected under the origin of this and that it has.